2012
DOI: 10.1108/17465721211207266
|View full text |Cite
|
Sign up to set email alerts
|

Despite the evidence – why are we still not creating more trauma informed mental health services?

Abstract: Purpose -Despite evidence that exposure to traumatic events can be an important antecedent to a range of serious and chronic mental health problems -it appears that within the British National Health Service at least, this is still not fully understood nor acted upon. This paper aims to examine this evidence and asks why these findings have not been fully implemented in terms of updating practice.Design/methodology/approach -A literature search was undertaken alongside relevant British DH policy. This resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…The barriers to asking about abuse have received a small amount of research attention , but the barriers to responding therapeutically following disclosures remain, apart from a misguided belief in some staff that psychosis is unrelated to adverse life events , unidentified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers to asking about abuse have received a small amount of research attention , but the barriers to responding therapeutically following disclosures remain, apart from a misguided belief in some staff that psychosis is unrelated to adverse life events , unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent qualitative studies in London, focussed specifically on domestic violence, have found that both service users and professionals believe that the medical diagnostic and treatment approach can be a barrier to inquiry and that service users experience mixed responses from staff following disclosure .…”
Section: Introductionmentioning
confidence: 99%
“…Supervisors (who are trained in detecting PTSD) can ask the supervisee appropriate questions that will ensure that the impact of trauma is less likely to be missed. The introduction of a screening tool for PTSD and an increased emphasis on trauma/PTSD in supervision will create a trauma-informed service, which is widely recognized as being of value in the US [18] and likely to be benefi cial in all mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Longden et al, 2012;Steel et al, 2005) and in the development of trauma-focused treatments for this population (Frueh et al, 2009;van den Berg et al, 2015). Epidemiological findings and therapeutic developments have contributed to recent calls for more trauma-informed mental health services (Rose et al, 2012), including the routine assessment of trauma history and current symptoms of posttraumatic stress. There is, therefore, a need for a brief screening instrument to identify those requiring trauma focussed interventions.…”
Section: Objectivesmentioning
confidence: 99%